Effectiveness of Intervention Program on Nurses’ Practices toward Diet Instructions for Orthopedic Patients Treated by Internal Fixation Devices - radhi, asmar; Atiyah, Hussein Hadi (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The study aims to determine the effectiveness of the intervention program on nurses’ practices toward diet instructions for orthopedic patients treated by internal fixation devices. Methodology: A quantitative approach using the per-experimental design was use to carry out the study in Misan Governorate / Al-Zaharawy Surgical Hospital / Orthopedic Wards. A non-probability, purposive sample of (30) nurses who work at the orthopedic ward. An interventional program was prepared and presented to the nurses and an observation checklist was constructed and used to evaluate their practices pre and pot the implementation of the program. Descriptive and inferential data analysis approached were used to analyze the study data. Results: the study presented that there are high significant differences between pre and post-test of the program presentation in all items of nurses’ practices toward patients’ dietary instructions. Conclusions: The study concluded the presented program has confirmed its effectiveness through the improvement in nurses’ practices regarding nutritional instruction for their patients at the orthopedic wards. Recommendations: The study recommends that the presented program can be used as a guide by all orthopedic nurses to update their skills with patients’ instructions and teaching them about the healthy nutrition and dietary habits.